Factors influencing knowledge and persuasion of financial regulators in the XBRL adoption process: The technological perspective - Ilias A.; Ghani E.K.; Azhar Z. (Sciedu Press, 2023)
This study examined the factors influencing XBRL adoption process among the Malaysian regulators in the financial reporting environment. Specifically, this study aims to examine the drivers and challenges in the knowledge and persuasion phase faced by the Malasyain regulators in their adoption process of XBRL. This study relied on two frameworks namely, the adoption process framework with specific focus on knowledge and persuasion, and the TOE framework focusing on technological context. Using a qualitative approach, this study found that within the technological context, relative advantage and trialability were the drivers in the knowledge and persuasion phase. This study also found that the regulators were aware of XBRL and had made efforts to understand the XBRL taxonomy. However, the regulators were needed to develop the internal capability of their organisations since different regulators have shown different factors during the knowledge and acquisition phase that is necessary for XBRL adoption. The findings in this study serve as guidelines to other regulators in Malaysia and other countries that have plans to adopt XBRL. Sciedu Press.